Pedagang Kaki Lima, Profil Entrepreneurship Sejati, Pelaku Ekonomi Kerakyatan, Ciptakan Jiwa Kewirausahaan Mandiri - Agus Prasetya (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2019)
This article is motivated by the fact that the existence of the Street Vendor (PKL) profession is a manifestation of the difficulty of work and the lack of jobs. The scarcity of employment due to the consideration of the number of jobs with unbalanced workforce, economically this has an impact on the number of street vendors (PKL) exploding ... The purpose of being a street vendor is, as a livelihood, making a living, looking for a bite of rice for family, because of the lack of employment, this caused the number of traders to increase. The scarcity of jobs, causes informal sector migration job seekers to create an independent spirit, entrepreneurship, entrepreneurship, with capital, managed by traders who are true populist economic actors. The problems in street vendors are: (1) how to organize, regulate, empower street vendors in the cities (2) how to foster, educate street vendors, and (3) how to help, find capital for street vendors (4) ) how to describe grief as a Five-Foot Trader. This paper aims to find a solution to the problem of street vendors, so that cases of conflict, cases of disputes, clashes of street vendors with Satpol PP can be avoided. For this reason, the following solutions must be sought: (1) understanding the causes of the explosions of street vendors (2) understanding the problems of street vendors. (3) what is the solution to solving street vendors in big cities. (4) describe Street Vendors as actors of the people's economy. This article is qualitative research, the social paradigm is the definition of social, the method of retrieving observational data, in-depth interviews, documentation. Data analysis uses Interactive Miles and Huberman theory, with stages, Collection Data, Display Data, Data Reduction and Vervying or conclusions.